Hybrid nanogel systems' recent development: manufacturing and applications in drug simultaneous delivery associated imaging approach - Humaira Sultana; Rabail Khaliq; Sameera Khurshid (AMMANIF, 2023)
Researchers in pharmacy are paying increasingly close attention to nanogel-based multifunctional drug delivery systems, particularly hybrid nanogels and multicompartment nanogels because they can lead to the achievement of a superior functionality through the synergistic property enhancement of each component. Even numerous agents with differing physicochemical properties can be delivered together thanks to the special hybrid and compartmentalized structures. More crucially, the stimuli-responsive properties may be easily included into the design of targeted drug release through gel systems.